Media Pembelajaran dalam Presfektif Hadis - Juniarti Iryani; Erwin Hafid; Arifuddin Ahmad (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The purpose of this research is to discuss the Islamic perspective on instructional media from the perspectives of Hadith and the Qur'an. The research method used is qualitative research with library research. The data was gathered through literature research, consisting of primary sources such as journals and other relevant readings related to thematic Hadith studies. The data management is entirely qualitative because the data encountered is in the form of verbal statements. The analysis method used is an "inductive" and comparative technique. The results of this research indicate that from the perspectives of the Qur'an and Hadith, instructional media suitable for the present era should follow Islamic values that promote goodness and distance themselves from wrongdoing. The instructional media used should also facilitate the learning process, be effective and efficient, and be in line with the rapid development of information technology.